Cultural value transformation in Anang Ardiansyah's song lyrics: a hermeneutic inquiry into banjar people's identity - Subroto, Wisnu; Nurdin, Encep Syarief; Subiakto, Bambang; Milyartini, Rita (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
This research deeply examines how the lyrics of Anang Ardiansyah's songs reflect the dynamics of character values and cultural identity of the people of Banjarmasin, by using Paul Ricoeur's hermeneutic approach which consists of 5 stages: (1) Theme Identification; (2) Naive Understanding; (3) Deep Interpretation; (4) Fusion Horizon that allows researchers to capture the various layers of meaning contained in song lyrics. This systematic analytical process provides a solid methodological framework to examine the representation of fundamental values such as Islamic religiosity, local wisdom, patriotism, and social solidarity, which are inherent in the cultural identity of the Banjar people. This research analyses the symbolic and metaphorical meanings in four selected songs: Bastamiyah, Bismillah Kata Bamula, Puhun Rambai, and Paris Barantai. Through a systematic interpretive analysis, which involves a layer-by-layer interpretation to decipher the text based on its cultural and historical context, this study reveals that the lyrics represent fundamental values such as Islamic religiosity, local wisdom, patriotism, and social solidarity that are deeply rooted in the cultural identity of the Banjar people. The findings show that the songs function as a medium for transmitting and preserving cultural values, bridging tradition and modernity. The significance of this research lies in identifying the mechanisms through which traditional art has a role in transmitting and preserving cultural values.